The Life of Dr Wyson Moses Kauzobafa Jele : Missionary to Zambia - Bwalya, Kelly (Book collections on Project MUSE., 2017)
This book explores the life and work of Rev Dr W.M.K. Jele, and his contribution to the Church of Central Africa Presbyterian, Synod of Zambia (CCAP). Jele served the CCAP Synod of Zambia from 1981 to 1988. From 1984 to 1988 he served as the first General Secretary of CCAP Synod of Zambia. The CCAP, Synod of Zambia traces its origin from the Free Church of Scotland. Since the 1880s it was known as the Free Church of Scotland of the Livingstonia Mission now CCAP Synod of Livingstonia. Its growth and development before 1984 depended on the missionaries from Scotland and CCAP Synod of Livingstonia in Malawi who could send missionaries to preach and administer the sacraments to the people of Northern Rhodesia, now Zambia.